1991
DOI: 10.1002/fld.1650130603
|View full text |Cite
|
Sign up to set email alerts
|

Variational formulation of three‐dimensional viscous free‐surface flows: Natural imposition of surface tension boundary conditions

Abstract: SUMMARYWe present a new surface-intrinsic linear form for the treatment of normal and tangential surface tension boundary conditions in C '-geometry variational discretizations of viscous incompressible free-surface flows in three space dimensions. The new approach is illustrated by a finite (spectral) element unsteady Navier-Stokes analysis of the stability of a falling liquid film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…This term includes both normal and tangential contributions. In [20] it was shown that this integral can be expressed as…”
Section: Relation To Free Surface Flowmentioning
confidence: 99%
“…This term includes both normal and tangential contributions. In [20] it was shown that this integral can be expressed as…”
Section: Relation To Free Surface Flowmentioning
confidence: 99%
“…In film problems we set V u = H 2 1 (Ω) and V b = H 1 (Ω), so that the no-slip boundary conditions (2.8) are enforced strongly, whereas the stress and insulating boundary conditions, (2.6), (2.7), and (2.9), must be imposed in a natural (weak) sense (e.g. [15,46]). Taking the free-surface amplitude into account, the full solution space is therefore V = V u × V b × C, which we equip with the direct-sum inner product (…”
Section: Weak Formulationmentioning
confidence: 99%
“…The key idea to effectively represent this term, first put forth by Ruschak [29] and later generalized to three-dimensional cases by Patera and Ho [21,22], is to employ a weak-form representation of the left-hand side of Equation (16), so that the mean curvature is expressed in terms of first derivatives of surface shape. We follow the ideas of Ruschak [29] and Patera and Ho [21,22] by invoking an identity from differential surface geometry [31] to express the first curvature s of the surface in terms of first-order derivatives. Here, we again show only the x-component of the derivation for brevity…”
Section: Finite Element Formulationmentioning
confidence: 99%